2003
DOI: 10.1021/la035285i
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Photorheological Effects of 6-Alkyl Coumarins in Aqueous Micellar Solutions

Abstract: Viscosities of aqueous micellar solutions of cetyltrimethylammonium bromide (CTAB) and Triton X-100 were measured in the presence and absence of coumarin derivatives, mainly 6-alkyl coumarins with alkyl substituents between methyl and cetyl. The coumarins generally increased the viscosity; the extent of the increase was specific:  alkyl chains of medium length showed the largest effects. In situ photodimerization of the coumarins led to a further rise in the viscosity for short alkyl substituents but to a drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
6
14
0
Order By: Relevance
“…The G 0 m values at different temperatures without OP-30 compare well with the literature values [27].…”
Section: Effect Of Temperature: Analysis Of Thermodynamics Of Micellisupporting
confidence: 85%
See 1 more Smart Citation
“…The G 0 m values at different temperatures without OP-30 compare well with the literature values [27].…”
Section: Effect Of Temperature: Analysis Of Thermodynamics Of Micellisupporting
confidence: 85%
“…During the determination of the intersection point (CMC) weight has been given to obtain two lines above and below the break (CMC) with different slopes and better regression coefficients. This method was standardized by determining the CMCs of CTAB and SDS, which compares well with literature values [27].…”
Section: Conductivity Measurementmentioning
confidence: 71%
“…The increase in conductivity of the solutions on addition of BAM indicates the interaction of BAM with the conventional surfactants [31,33]. The CMC values in absence of BAM of both the pure surfactants measured from conductivity data are found to be in good agreement with the values available in the literature [31][32][33]. The decrease in CMC and the degree of dissociation of the mixture with the addition of the non-ionic gemini surfactant (Table 1) suggest a synergistic interaction between the ionic surfactants and BAM.…”
Section: Critical Micellar Concentration From Conductivity and Absorbsupporting
confidence: 80%
“…This intersection point (CMC) is determined by selecting two lines above and below the break (CMC) having comparable difference in slope and better regression coefficient. This method was standardized by determining the CMC's of CTAB and SDS, which compares well with the literature values [31][32][33].…”
Section: Conductivity Measurementmentioning
confidence: 66%
“…The authors further developed systems with photo-switchable viscosity by introducing coumarin derivatives into the aqueous solutions of Triton X-100 and CTAB [10]. They found that coumarins generally increased the viscosity, but the extent of the increase was specific: alkyl chains of medium length showed the largest effect.…”
Section: Monomerization/dimerization Of a Light-sensitive Additivementioning
confidence: 99%